Inbreeding Depression Test in Phenotypic Characters of Maize Plants from Selfing and Open Pollinated - fitri ekawati; Doni Hariandi; Irfan Suliansyah (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2021)
The initial step in the assembly of hybrid maize is the formation of inbred lines. This research aims to see the differences in phenotypic characters and to determine the percentage of inbreeding depression between selfing and open-pollinated plant populations. Research activities have been carried out in the cornfield of Nagari Sitiung, Sitiung District, Dharmasraya Regency, West Sumatra. The materials used were F2 maize selected from a cross between BSM0729S3 and BAP27799 and maize S4 from BSM0729S3 (female parent). The research was conducted using a T-test, namely open-pollinated (T1) and selfing (T2). After the T-test was performed, the percentage of inbreeding depression was calculated for each observation variable. The results showed that the open-pollinated treatment was significantly different from the selfing treatment on the variables of plant height, ear height, anthesis time, silking time, harvesting age, ear weight per plant, length and diameter of the ear, kernel row number, and intensity of anthocyanin staining on hair, tassels, and roots. The magnitude of the decrease in vigor in the open-pollinated treatment was smaller than the selfing treatment on all observed variables except for the anthocyanin intensity variable in tassel and roots. Therefore, it is necessary to do further selfing on the S4 population to obtain uniform pure lines and mass selection on the F2 population to produce a uniform maize population.